2005
DOI: 10.1002/adem.200500084
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Materials for Advanced Solid Oxide Fuel Cells

Abstract: Solid oxide fuel cells are ceramic fuel cells that convert chemical into electrical energy at temperatures between 650 °C and 1000 °C. Today, this type of fuel cell is receiving ever‐increasing attention due to its principle capability to provide electricity from both fossil and renewable fuel sources. Systems are currently under development for a variety of applications, including small and large‐scale stationary combined heat and power systems, and power generation systems in the automotive area. Materials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…A spray-pyrolysis device with a capacity of up to 3 kg powders per day was established for powder synthesis [11]. The set-up consists of an electrically heated furnace with a stainless-steel vessel equipped with a spraying nozzle in the center of the top cover.…”
Section: Methodsmentioning
confidence: 99%
“…A spray-pyrolysis device with a capacity of up to 3 kg powders per day was established for powder synthesis [11]. The set-up consists of an electrically heated furnace with a stainless-steel vessel equipped with a spraying nozzle in the center of the top cover.…”
Section: Methodsmentioning
confidence: 99%
“…performance. This problem can be resolved by increasing the Mn concentration and keeping fabrication temperature <1300 °C [10,12,42,[45][46][47][48][49][50]. LSM has negligible oxygen ion conductivity at 900 °C with high electronic conductivity.…”
Section: Cathodementioning
confidence: 99%
“…In comparison, La 6.4 Sr 1.6 Cu 8 O 20˘8 gives very good electrical conductivity but it reacts with YSZ at temperatures above 600˝C [58]. More information on cathode materials can be accessed through detailed reviews [10,12,25,50].…”
Section: Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Several excellent reviews [5][6][7][8][9][10][11] have reported on the development of conventional solid oxide fuel cell materials and these details will only be briefly summarised here.…”
mentioning
confidence: 99%